2020
DOI: 10.1073/pnas.1921446117
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic role of oxytocin in medaka mate choice

Abstract: Oxytocin is a central neuromodulator required for facilitating mate preferences for familiar individuals in a monogamous rodent (prairie vole), irrespective of sex. While the role of oxytocin in mate choice is only understood in a few monogamous species, its function in nonmonogamous species, comprising the vast majority of vertebrate species, remains unclear. To address this issue, we evaluated the involvement of an oxytocin homolog (isotocin, referred herein as oxt) in mate choice in medaka fish (Oryzias lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…For example, oxt expression in the telencephalon and hypothalamus was not different between WT and scg2a −/− ;-scg2b −/− males and females. Importantly, using oxt and oxtr1 mutations in medaka, Yokoi et al (51) demonstrated that oxt function is required for mate choice based on familiarity recognition. They concluded that oxt is important for female recognition of familiar males.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxt expression in the telencephalon and hypothalamus was not different between WT and scg2a −/− ;-scg2b −/− males and females. Importantly, using oxt and oxtr1 mutations in medaka, Yokoi et al (51) demonstrated that oxt function is required for mate choice based on familiarity recognition. They concluded that oxt is important for female recognition of familiar males.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to recognize another individual is crucial for social interaction [28], emerges very early in development [29,30], is conserved across species [28], and is linked to the oxytocin (OXY) system [31,32]. Humans, like other primates, recognize other individuals mostly by their face [33][34][35], which has evolved to signal individual identity [36].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sexual behavior, in studies where the regulation of sex hormones was altered, changes in sexual behavior were primarily related to courtship, such as the frequencies of following, dancing, and latency from the first courtship (Hiraki-Kajiyama et al, 2019;Oshima et al, 2003). Additionally, when brain regulators were altered, such as arginine-vasotocin (Yokoi et al, 2015), oxytocin ligand (oxt) (Yokoi et al, 2020) and TN-GnRH3 (Okuyama et al, 2014), changes in courtship display and sexual motivation, latency to mating and number of courtships displays, and latency to mating, were observed, respectively. None of these courtship actions changed in the male ndrg1b mutants, leading us to consider whether the specific mating actions of quivering and convulsions are exclusively related to the lower number of spermatogonia and spermatozoa in males.…”
Section: Discussionmentioning
confidence: 99%